2018
DOI: 10.17344/acsi.2017.3826
|View full text |Cite
|
Sign up to set email alerts
|

The Cl Functionalized Aluminum Nitride (AlN) and Aluminum Phosphide (AlP) Nanocone Sheets as Hydrogen Selenide (H2Se) Sensor: a Density Functional Investigation

Abstract: The adsorption of H 2 Se molecule on AlN-NCS and AlP-NCS surfaces were investigated by using of DFT calculations. The potentials of Cl-functionalized AlN-NCS and AlP-NCS for H 2 Se adsorption were examined. All processes of H 2 Se-adsorption on considered nanocone sheets were exothermic reactions. The calculated |E ad | amount of complex H 2 Se with AlP-NCS was higher than AlN-NCS. The functionalization of considered nanocone sheets with Cl atom increase |E ad | amount of H 2 Se. Results reveal that, obtained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 41 publications
(47 reference statements)
0
2
0
Order By: Relevance
“…In fact, selenium is an environmentally and biologically essential element, and hydrogen selenide (H 2 Se) is found to be an important metabolite of Se compounds in living cells. , H 2 Se is known to display chemical markers different from those of hydrogen sulfide (H 2 S). Especially, H 2 Se plays a significant role related to the nanomaterials, such as in the synthesis of CdSe and CuSe nanocrystals, by directly reacting with metal ions. A recent study reported that the adsorption of H 2 Se on the AlN and AlP nanocone sheets is favorable . H 2 Se can be also adsorbed on the ZnO, TiO 2 , and Zn 2 TiO 4 surfaces to facilitate its dehydrogenation. , The reactions of H 2 Se with laser-ablated actinide metal atoms produce H 2 AnSe (An = Th, U), which have the unusual highly polarized actinide–selenium triple bond (Andrews, Dixon, and coworkers) …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, selenium is an environmentally and biologically essential element, and hydrogen selenide (H 2 Se) is found to be an important metabolite of Se compounds in living cells. , H 2 Se is known to display chemical markers different from those of hydrogen sulfide (H 2 S). Especially, H 2 Se plays a significant role related to the nanomaterials, such as in the synthesis of CdSe and CuSe nanocrystals, by directly reacting with metal ions. A recent study reported that the adsorption of H 2 Se on the AlN and AlP nanocone sheets is favorable . H 2 Se can be also adsorbed on the ZnO, TiO 2 , and Zn 2 TiO 4 surfaces to facilitate its dehydrogenation. , The reactions of H 2 Se with laser-ablated actinide metal atoms produce H 2 AnSe (An = Th, U), which have the unusual highly polarized actinide–selenium triple bond (Andrews, Dixon, and coworkers) …”
Section: Introductionmentioning
confidence: 99%
“…12−15 A recent study reported that the adsorption of H 2 Se on the AlN and AlP nanocone sheets is favorable. 16 H 2 Se can be also adsorbed on the ZnO, TiO 2 , and Zn 2 TiO 4 surfaces to facilitate its dehydrogenation. 17,18 The reactions of H 2 Se with laser-ablated actinide metal atoms produce H 2 AnSe (An = Th, U), which have the unusual highly polarized actinide−selenium triple bond (Andrews, Dixon, and coworkers).…”
Section: Introductionmentioning
confidence: 99%